PENGGUNAAN METODE HOUSE OF RISK UNTUK ANALISIS FAKTOR KETERLAMBATAN DAN PENYUSUNAN STRATEGI PENANGANAN: STUDI KASUS PEMBANGUNAN MALL - Saputra, Ramdhan Yundra; Baihaqi, Imam (Universitas Nahdlatul Ulama Surabaya, 2018)
In the work plan there are often operational problems that hinder the completion of a project such as lack of resources, improper resource allocation, delays in project implementation and other issues beyond the schedule in the work plan. The same happened to the mall development project experiencing operational problems. Project delays may come from service providers as well as from users of services or other parties. Therefore this thesis aims to analyze the factors causing the delay in completion of the mall development project. The method used in analyzing the problem in this project is house of delay which serves to analyze data of cause of delay. From the result of 5 delay events, 13 delay agents are then searched aggregate delay potential (ADP) value to determine 3 main problems causing delays in this project. Based on the analysis using the HOR method, found that the three main causes of the delay of mall development is the image changes, lack of coordination by the owner, and the addition of the scope of work. These 3 problems can be minimized by making good communication and coordination with the owner, creating procedures for making and changing pictures, creating a comprehensive check list.